Pengembangan Modul Eksperimen Berbasis Lembar Kerja Siswa (LKS) untuk Meningkatkan Aktivitas dan Hasil Belajar IPA pada Materi Perubahan Wujud Benda - Ida Rahmawati; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study presents a systematic literature review (SLR) on the development of a Student Worksheet (SW)-based experimental module to improve science learning activities and outcomes on the topic of changes in state of matter. The SLR method follows the PRISMA 2020 guidelines for the identification, selection, and synthesis of empirical studies and R&D published between 2020 and 2025. Searches were conducted through Google Scholar, academic repositories, and education journals. The synthesis results indicate that experimental SW that focus on science process skills, guided inquiry, and multimedia integration consistently improve student learning activities and outcomes. The SW design that includes structured experimental steps, safety guidelines, assessment rubrics, and student reflections provides the greatest contribution to effectiveness. This article concludes with recommendations for SW experimental design for teachers and researchers. Keywords : Student worksheets, Science experiments, Changes in the state of matter, Learning activities, SLR learning outcomes Abstrak Penelitian ini menyajikan tinjauan sistematik literatur (Systematic Literature Review – SLR) mengenai pengembangan modul eksperimen berbasis Lembar Kerja Siswa (LKS) untuk meningkaykan aktivitas dan hasil belajar IPA pada materi perubahan wujud benda. Metode SLR mengikuti pedoman PRISMA 2020 untuk identifikasi, seleksi, dan sintesis studi empiris serta R&D yang dipublikasikan antara 2020-2025. Penelusuran dilakukan melalui Google Scholar, repositori akademik, dan jurnal pendidikan. Hasil sintisesis menunjukkan bahwa LKS ekperimen yang berorientasi pada keterampilan proses sains, guided inquiry,dan integrasi multimedia secara konsisten meningkatkan aktivitas dan hasil belajar siswa. Desain LKS yang memuat langkah eksperimen terstruktur, panduan keselamatan, rubrik penilaian, dan refleksi siswa memberi kontribusi terbesar terhadap efektivitas. Artikel ini diakhiri dengan rekomendasi desain LKS eksperimen bagi guru dan peneliti. Kata Kunci : Lembar kerja siswa, Eksperimen ipa, Perubahan wujud benda, Aktivitas belajar, Hasil belajar SLR